STOCK LIQUIDITY AND PERFORMANCE OF SELECTED QUOTED FIRMS IN NIGERIA: CASE STUDY OF FAST-MOVING CONSUMER GOODS (FMCG) (UNIZIK Journal of Marketing, 2025)
This study investigated the impact of stock liquidity of performance of selected quoted firms, in the Fast-Moving Consumer Goods Sector (FMCG) in Nigeria. The study selected ten (10) firms based on their level of liquidity, five (5) most liquid firms and Five (5) least liquid respectively, spanning from year 2006-2020. It adopted explanatory research design, the dependent variable firm performance was Proxied by Return on Equity (ROE) while stock liquidity was Proxied by trade based measure( Ahmihud Illiquidity ratio), with control variables which include Firm size Proxied by Market Capitalization, Corporate Governance Proxied by Board size , Stock Return Volatility, Proxied by Variance of Stock Return  and Inflation Rate .Pre estimation carried out include ; Bruesch-Pagan (BP) LM Test which showed existence of cross sectional dependency test, and Kao Cointegration test revealed existence of long run relationships. The study deployed the Non-Linear Panel Auto Regressive Distributed Lag (NARDL) to estimate the model, and Pooled Mean Group (PMG) was specifically used. We had three sample categories; Full Sample, High Liquid and Low Liquid. Results revealed that in the short run, variations in AILQ both positive AILQ+ and AILQ- have an effect on ROE. In the long run, both positive and negative changes in AILQ have a substantial long-term impact in ROE. However, the negative change seems to have a stronger influence. This study concludes that firm performance is greatly impacted by stock liquidity, which shows that fluctuations in stock liquidity would greatly impact an organization's profitability. Thus, validating the findings of Karim and Rashid (2020). This study recommends that the government should adopt rules and regulations that are more sector-specific in order to influence the Nigerian Stock Market and enable investors to make investments in areas that are essential to the country's economy as a whole. This can be accomplished by giving more security to crucial yet data-dictated areas.
Keywords: Stock Liquidity, Firm Performance, Return on Equity, Ahmihud Illiquidity